Synthesis and Antiviral Evaluation of 2′,3′-β-C-Disubstituted Nucleoside Analogue ProTides to Test a Conformational Model of Potency Against Hepatitis C - Dentmon, Zackery W.; Butch, Christopher J.; Gold, Hannah B.; Liotta, Dennis C. (Synlett, 2022)
An analysis of nucleoside active metabolite potencies against Hepatitis C virus (HCV) versus their parent ground-state energetic conformational bias as calculated by density functional theory suggested that nucleotides with a small difference between their antipodal energies are more likely to have potent antiviral activity compared to those with larger energetic differences. This energetic conformational bias was thought to be manipulated with substitutions along the ribofuranose ring. From 2′-C-methyluridine, a representative nucleoside with fair anti-HCV activity, two C3′ modifications in particular (ethyne and methyl) showed contrasting antipodal biases relative to each other while originating from a common synthetic intermediate, allowing a test of reasonable extremes of the computational model with a divergent nine-step synthesis. Antiviral activity of the compounds contradicted that suggested by the model, indicating a need for further refinement with additional biostructural considerations.
Keywords: nucleosides; hepatitis C; prodrugs; antiviral agents; protides; density functional theory